DOMINANT RISK FACTORS FOR THE INCIDENCE OF "ACUTE RESPIRATORY INFECTION” "ARI” IN TODDLERS: Faktor Risiko Yang Dominan Terhadap Kejadian "Infeksi Pernapasan Akut” "Ari” Pada Balita - Ginting, Johannes Bastira; Anggraini, Nazila; Syukriyah Syaputri Pasaribu, Bella; Nur, Rehan; Buenita, Buenita (Jurnal Berkala Epidemiologi, 2024)
Background: Acute Respiratory Infection (ARI) is a contagious illness affecting diverse age groups, including toddlers, and is among the top ten reasons for Community Health Center visits. Purpose: This study aims to analyze the influence of dominant risk factors on the incidence of ARI in toddlers. Methods: This study used an observational, analytic-cross sectional approach, at Puskesmas Kampung Lalang, Medan, in 2023. The total population was 394 toddlers (aged 0-59 months).  In the determination of the number of samples using the sample size estimation formula, 198 samples were obtained by purposive sampling. Data analysis used Chi-Square test and Multiple Logistic Regression Enter Methods, with a significance level of 95%. Results: The results showed that the variables of Vitamin A administration (OR = 0.27, 95% CI: 0.10-0.77) and immunization status (OR = 0.36, 95% CI: 0.14-0.93) were associated with a decreased risk of ARI in toddlers. In contrast, exclusive breastfeeding (OR = 2.35, 95% CI: 1.11-5.01) was associated with increased risk, while the physical environment of the house (OR = 2.92, 95% CI: 1.28-6.64) was associated with increased risk of ARI. Conclusion: Vitamin A administration and immunization reduce the risk of respiratory tract infection among under-fives at Puskesmas Kampung Lalang. Exclusive breastfeeding and home conditions increased the same risk. Improving these risk factors is essential to reduce the prevalence of childhood respiratory infections in the area.